UV-crosslinked poly(arylene ether sulfone) – LAPONITE® nanocomposites for proton exchange membranes. Issue 45 (30th May 2017) - Lee, Sun Hwa; Lee, Won Jun; Kim, Tae Kyoung; Bayazit, Mustafa K.; Kim, Sang Ouk; Choi, Yeong Suk
Abstract : UV-crosslinked sulfonated poly(arylene sulfone)/clay nanocomposites are fabricated by incorporating UV-crosslinkable monomers, bridge molecules, and clay nanofillers for high performance proton exchange membrane fuel cells. Abstract : The dimensional stability and barrier properties of proton exchange membranes are critical issues for high-performance proton exchange membrane fuel cells (PEMFCs). In this work, we introduce a viable and effective strategy for preparing high proton-conductive polymer membranes with remarkable dimensional stability and barrier properties. Sulfonated poly(arylene sulfone)s (sPASs) with a UV-crosslinkable monomer, 2, 2′-diallylbisphenol A (DABPA), is successfully synthesized via condensation polymerization, showing competitive molecular weights and sulfonation degrees to the neat polymer. Crosslinked nanocomposite membranes can be fabricated by incorporating soft bridge molecules and exfoliated LAPONITE® nanofillers, and subsequent UV-crosslinking. The sPAS–LAPONITE® nanocomposite membranes show greatly improved dimensional stabilities and barrier properties including remarkably reduced swelling ratio in solvent or methanol aqueous solutions. These enhanced properties lead to excellent performance in a direct methanol fuel cell (DMFC) test, surpassing that of a commercially available Nafion membrane based devices.